Effect of Financial Regulations on Accountability of Some Selected Public Organizations in Nigeria - Mohammed, Abdullahi; Buba, Adamu; Ahmed, Uthman Omale (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The Federal Government of Nigeria has implemented reforms to combat corruption and promote public accountability in public service. The Federal Government Financial Regulations aim to achieve this by promoting transparency and accountability. This study examines the impact of financial regulations on accountability, focusing on compliance with internal audit reviews and the enforcement of sanctions for breaches resulting in government losses. The study uses primary data from interviews with staff at the National Identity Management Commission (NIMC) and National Airspace Research and Development Agency (NASRDA) and quantitative data collection. Results show that strict compliance with internal audit reviews significantly improves accountability in the area, leading to public trust in financial transactions. Additionally, strict enforcement of sanctions on breaches resulting in government losses also enhances accountability. The study suggests regularly providing a detailed internal audit review time table to staff and unit heads for proper preparation. Prompt reporting of anomalies is crucial. Top leadership should outline consequences for non-observance and strengthen internal controls to ensure checks and balances in audit reviews. Lastly, the study suggests imposing stiffer sanctions on breaches causing government losses to deter erring staff and strictly based on financial regulations.
Keywords: Accountability, Internal audit reviews, Financial Regulations, Sanctions, Public service